A large-scale forward genetic screen for maize mutants with altered lignocellulosic properties - Wang, Shaogan; Robertz, Stefan; Seven, Merve; Kraemer, Florian; Kuhn, Benjamin M.; Liu, Lifeng; Lunde, China; Pauly, Markus; Ramírez, Vicente (Frontiers in Plant Science, 2023)
Grasses include some of the most widely cultivated crop species such as maize, rice, sorghum, or wheat. After harvesting the grain, large amounts of residual lignocellulosic biomass represent a renewable feedstock for the conversion to biofuels and other commodity chemicals. The dominant impediment for the use of these feedstocks is the recalcitrance of the lignocellulsic composite material to degradation into fermentable sugars. The development of efficient pipelines for the bioconversion of grass lignocellulosic feedstocks is challenging due to the limited understanding of the molecular mechanisms controlling the synthesis, deposition, and degradation of the varying polymers unique to grass lignocellulosics. Here, we describe a large-scale forward genetic approach resulting in the identification of a collection of chemically mutagenized maize mutants altered in their saccharification yield, i.e. the amount of lignocellulosic glucose (Glc) released by means of enzymatic hydrolysis. These mutants, termed candy-leaf (cal), show no obvious plant growth or developmental defects despite associated differences in their lignocellulosic composition. The identified cal mutants are a valuable tool not only to understand recalcitrance of grass lignocellulosics to enzymatic deconstruction but also to decipher grass-specific aspects of cell wall biology once the genetic basis, i.e. the location of the mutation, has been identified.